Insulation Coordination System 150kV Substation and Transmission Line against Lightning Surge Interference in a Nickel Smelting Plant - Samad, Busyairi; Manjang, Salama; Kitta, Ikhlas; Utamidewi, Dianti; Amri, Arham (Bright Publisher, 2024)
Related with the increasing demand for electrical energy at nickel smelting plant, a highly reliable electric power system is needed to be able to supply important loads such as electric furnaces and auxiliary equipment. The electric power system delivers electrical power to consumers through substations and transmission lines. The distribution of electrical power through high voltage overhead lines (SUTT) sometimes goes through areas with a high enough lightning strike potential that it can cause sudden blackouts due to direct strikes and back flashovers. Therefore, it is necessary to insulation coordination of the substation and transmission line to avoid damage to electrical equipment. This research aims to determine the magnitude of the voltage due to lightning strikes on GSW and Conductor by varying the location of the lightning protection system on 150 kV overhead line which is useful for obtaining isolation coordination systems on transmission lines and substations in the nickel smelting industry. which is useful for obtaining isolation coordination systems on transmission lines and substations in the nickel smelting plant. This research was carried out by selecting lightning strikes in the current strike of 100 kA on transmission line with simulation use device ATP draw software. This research showed that the installation of lightning protection equipment on high-voltage overhead lines and transmission towers resulted in a significant voltage drop due to lightning strikes lowering under BIL existing insulators.